2019
DOI: 10.3390/nu11030497
|View full text |Cite
|
Sign up to set email alerts
|

Green Coffee Extract Improves Cardiometabolic Parameters and Modulates Gut Microbiota in High-Fat-Diet-Fed ApoE-/- Mice

Abstract: Chlorogenic acids (CGA) are the most abundant phenolic compounds in green coffee beans and in the human diet and have been suggested to mitigate several cardiometabolic risk factors. Here, we aimed to evaluate the effect of a water-based standardized green coffee extract (GCE) on cardiometabolic parameters in ApoE-/- mice and to explore the potential underlying mechanisms. Mice were fed an atherogenic diet without (vehicle) or with GCE by gavage (equivalent to 220 mg/kg of CGA) for 14 weeks. We assessed severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 103 publications
2
18
0
Order By: Relevance
“…In accordance with other reports [ 19 , 20 ], HFD induces body weight gain in association with the increased of plasma TG level and decreased HDL/LDL ratio. The consequences of the HFD are also evident at hepatic and cardiovascular level.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with other reports [ 19 , 20 ], HFD induces body weight gain in association with the increased of plasma TG level and decreased HDL/LDL ratio. The consequences of the HFD are also evident at hepatic and cardiovascular level.…”
Section: Discussionsupporting
confidence: 93%
“…Glucagon can increase the hepatic adipose triglyceride lipase activity, intrahepatic lipopolysis and hepatic acetyl-CoA content, and then stimulates hepatic gluconeogenesis, while it also increases mitochondrial fat oxidation [ 32 ]. Epinephrine is considered a master regulator of lipolysis [ 33 ]. The study found that mice that could not produce epinephrine had normal metabolism on a normal 14% fat diet, but when fed a high-fat diet, they developed hyperglycemic and IR [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since various diseases have been associated with oxidative stress, dietary PPs reduce the effects caused by excessive ROS or other nitrogen species. By neutralizing the free radicals via donating an electron and as direct radical scavengers of the lipid peroxidation chain reactions, PPs eradicate the oxidative stress [ 12 ]. Phenolic acids and flavonoids, including anthocyanins, procyanidins, quercetin, catechins, curcumin, and ellagic acids, have their role in obesity and weight management [ 13 ].…”
Section: Biological Role Of Ppsmentioning
confidence: 99%